Tropical Disease Prevention and Control: Is It Now Knowledge Management Era? - Sudiarno, Adithya; Rahman, Arief; Partiwi, Sri Gunani (Institute of Topical Disease Universitas Airlangga, 2010)
Indonesia is the part of developing Asian countries, until now still not declared free from various types of tropical diseases. Whereas, several years ago Indonesia has declared free from various kinds of tropical diseases, but in fact, tropical diseases up to now still cannot be eliminated. Moreover the prevalence rates of tropical diseases tended to increase from year to year. One of the reasons Indonesia is a tropical climate, but in fact we are not able to control the climate. In this condition, what we can do is to raise public awareness so the spread of the disease can be controlled. It was time for an early awareness efforts conducted in a participatory manner by all stakeholders. In this case, stakeholders can be health practitioners, researchers, policy makers (official), and even the citizens. Participatory awareness can be enhanced if we have an integrated system that can accommodate all knowledge about tropical disease. The knowledge consists of characteristic about disease, potential risk, how to cure, how to isolate disease in community, and absolutely important is how to prevent of illness, etc. This paper aims to propose an integrated system called Tropical Disease Knowledge Management System (TDKMS) for enhancing the participatory awareness.